2018
DOI: 10.1016/j.hbrcj.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of corroded bonded partially prestressed concrete beams

Abstract: Prestressed concrete is widely used in the construction industry in buildings. And corrosion of reinforcing steel is one of the most important and prevalent mechanisms of deterioration for concrete structures. Consequently the capacity of post-tension elements decreased after exposure to corrosion. This study presents results of the experimental investigation of the performance and the behavior of partially prestressed beams, with 40 and 80 MPa compressive strength exposed to corrosion. The experimental progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…It was indicated that fatigue cracks initiate and propagate rapidly around corrosion pits under cyclic loading, and the fatigue failure of prestressing wires at the minimum section where corrosion pits formed was induced by cyclic loading. Moawad et al [ 34 ] studied the behavior of partially prestressed corroded bonded concrete beams. Results indicated that the semi-prestressed concrete beam with the higher compressive strength was more resistant to corrosion than the beam with the lower compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that fatigue cracks initiate and propagate rapidly around corrosion pits under cyclic loading, and the fatigue failure of prestressing wires at the minimum section where corrosion pits formed was induced by cyclic loading. Moawad et al [ 34 ] studied the behavior of partially prestressed corroded bonded concrete beams. Results indicated that the semi-prestressed concrete beam with the higher compressive strength was more resistant to corrosion than the beam with the lower compressive strength.…”
Section: Introductionmentioning
confidence: 99%